Professional counseling excellence through leadership and advocacy - Chang, Catherine (Routledge, 2012)
"This book is intended as a resource for counseling students and educators to help incorporate leadership and advocacy training into the counseling curriculum, based on the new standards set forth by CACREP. It identifies the historical context of leadership and advocacy, provides a framework from which to understand these concepts, and provides concrete examples of leadership and advocacy happening in the field today"-- Provided by publisher